2018
DOI: 10.3389/fnagi.2018.00001
|View full text |Cite
|
Sign up to set email alerts
|

Weight Loss and Malnutrition in Patients with Parkinson's Disease: Current Knowledge and Future Prospects

Abstract: Parkinson's Disease (PD) is currently considered a systemic neurodegenerative disease manifested with not only motor but also non-motor symptoms. In particular, weight loss and malnutrition, a set of frequently neglected non-motor symptoms, are indeed negatively associated with the life quality of PD patients. Moreover, comorbidity of weight loss and malnutrition may impact disease progression, giving rise to dyskinesia, cognitive decline and orthostatic hypotension, and even resulting in disability and mortal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
180
1
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 178 publications
(195 citation statements)
references
References 208 publications
(272 reference statements)
10
180
1
4
Order By: Relevance
“…Thus, the chewing problems may also contribute to the weight loss that is often seen in PD. 33 In the present study, almost half of the patients reported chewing and swallowing problems in the NOT-S.…”
Section: Discussion and Con Clus I Onsupporting
confidence: 46%
See 1 more Smart Citation
“…Thus, the chewing problems may also contribute to the weight loss that is often seen in PD. 33 In the present study, almost half of the patients reported chewing and swallowing problems in the NOT-S.…”
Section: Discussion and Con Clus I Onsupporting
confidence: 46%
“…33 In the present study, almost half of the patients reported chewing and swallowing problems in the NOT-S. non-pharmacological aids in PD. 33 In the present study, almost half of the patients reported chewing and swallowing problems in the NOT-S. non-pharmacological aids in PD.…”
Section: Discussion and Con Clus I Onmentioning
confidence: 45%
“…In fact, a decrease in olfactory function that occurs for a long period of time can decrease emotional memory of external stimuli, as reported in our previous work [16]. Instead, fatigue is one of the NMSs that affects about 50% of PD patients [10,20] and seems to be related to anxiety and apathy [20,45].…”
Section: Discussionmentioning
confidence: 59%
“…The weight change in PD patients is associated to worsening quality of life, infections, malnutrition, cognitive decline and bone fracture. Moreover, Ma and Colleagues [10] suggested that the body weight loss is related to a low density of nigrostriatal dopamine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation